?SYNTHESIS AND PROPERTIES OF MALEIC ANHYDRIDE· CROTONIC ACID·VINYL ACETATE TERPOL YMER (Biological Sciences - PJSIR, 1994)
Free radical terpolymerization of maleic anhydride (in the form ofhalfestcr of maleic acid) crotonic acid and vinyl acetate has been accomplished at 75-80° using benzoyl peroxide as initiator. It has been observed that three monomers polymerise simultaneously and form terpolymer in all monomeric ratios. Terpolymers of 8394-18434 molecular weight are obtained. These are white solid substances soluble in most of organic solvents that softens at 70-90°. The refractive index ofterpolymer samples ranges 1.3610-1.3635. The terpolymers may be used in the preparation of hair spray as the film forming agent.